2012
DOI: 10.1007/s10561-012-9306-4
|View full text |Cite
|
Sign up to set email alerts
|

Effects of ionizing radiation and preservation on biomechanical properties of human costal cartilage

Abstract: Tissue banks around the world store human cartilage obtained from cadaveric donors for use in diverse reconstructive surgical procedures. To ensure this tissue is sterile at the time of distribution, tissues may be sterilized by ionizing radiation. In this work, we evaluate the physical changes in deep frozen costal cartilage (-70 °C) or costal cartilage preserved in high concentrations of glycerol (>98 %) followed by a terminal sterilization process using ionizing radiation, at 3 different doses (15, 25 and 5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
2

Year Published

2013
2013
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 16 publications
0
5
2
Order By: Relevance
“…According to ISO 11137 [43] a typical or standard sterilization dose is placed within 15 and 25 kGy with most products sterilised by radiation nowadays being validated for such doses. However, there is evidence in literature that irradiation doses of 25 kGy may change the chemical structure of certain compounds [50], which we herein demonstrated not to hold true in the case of β-alanine, even at doses up to 40 kGy.…”
Section: Discussioncontrasting
confidence: 71%
“…According to ISO 11137 [43] a typical or standard sterilization dose is placed within 15 and 25 kGy with most products sterilised by radiation nowadays being validated for such doses. However, there is evidence in literature that irradiation doses of 25 kGy may change the chemical structure of certain compounds [50], which we herein demonstrated not to hold true in the case of β-alanine, even at doses up to 40 kGy.…”
Section: Discussioncontrasting
confidence: 71%
“…In contrast to other studies on hyaline cartilages that show high water content (up to 85%), in this work, cartilages have showed an average of 42 wt % water content [50]. It is reasonably plausible that a given donor can present different water content within the body parts due to natural dehydration.…”
Section: Tp1contrasting
confidence: 75%
“…21 Martinho et al demonstrated that variations in preparation and irradiation dose significantly alter the biochemical properties of costal cartilage, and Donald et al postulated that the variation in resorption rates may be due to the physical properties of the cartilage based on the radiation dose at each institution, with high-dose radiation being associated with significantly less stiffness. 42,43 AlloWash-XG used at this institution is sterilized with low-dose radiation in a chamber, exposing tissue to a range of 15 to 18 kGy at low temperature (–80°C, dry ice temperature) to reduce free radical formation. It has been found that irradiation levels <18 kGy have the lowest risk of clinical failure and need for revision.…”
Section: Discussionmentioning
confidence: 99%
“…Suh et al performed a large retrospective review of 323 patients and found complications rates for irradiated homologous costal cartilage of 1.2% resorption and 0.6% warping, with most complications occurring for septal extension grafts 21 . Martinho et al demonstrated that variations in preparation and irradiation dose significantly alter the biochemical properties of costal cartilage, and Donald et al postulated that the variation in resorption rates may be due to the physical properties of the cartilage based on the radiation dose at each institution, with high‐dose radiation being associated with significantly less stiffness 42 , 43 . AlloWash‐XG used at this institution is sterilized with low‐dose radiation in a chamber, exposing tissue to a range of 15 to 18 kGy at low temperature (–80°C, dry ice temperature) to reduce free radical formation.…”
Section: Discussionmentioning
confidence: 99%